Validitas E-Modul Interaktif Menggunakan Smart Apps Creator Bermuatan Pendekatan Kontekstual tentang Materi Ekosistem untuk Peserta Didik di SMA: (Validity of Interactive E-Modules Using Smart Apps Creator Containing Contextual Teaching and Learning about Ecosystem Materials for High School Students) - Elsa Suci Ramanda; Relsas Yogica; Rustiono Rustiono; Ganda Hijrah Selaras (BIODIK, 2023)
The development of Science and Technology (IPTEK) provides changes in the field of education, especially in the learning media used. Now learning media can be presented in digital form which provides opportunities for students to learn independently, one of these media is e-module. E-modules are teaching materials that are packaged in digital form and presented in a more interactive form. The purpose of this study was to determine the validity of interactive e-modules using Smart Apps Creator containing a contextual teaching and learning about ecosystem materials for high school students. This research is a development research with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research subjects were 2 Biology lecturers, FMIPA UNP, 1 Biology teacher at SMAN1 Payakumbuh. The data obtained in this study are in the form of observation data and validity data. This research produces an Interactive E-Modul Using Smart Apps Creator with a contextual approach to Ecosystem Materials for High School Students. abstrak. Perkembangan Ilmu Pengetahuan dan Teknologi (IPTEK) memberikan perubahan pada bidang pendidikan terutama pada media pelajaran yang digunakan. Sekarang media pelajaran bisa disajikan dalam bentuk digital yang memberikan kesempatan kepada peserta didik untuk belajar secara mandiri, satu diantara media tersebut adalah e-modul. E-modul merupakan bahan ajar yang dikemas dalam bentuk digital dan sajikan lebih dalam bentuk yang lebih interaktif. Tujuan dari penelitian ini adalah untuk mengetahui validitas e-modul interaktif menggunakan Smart Apps Creator bermuatan pendekatan kontekstual tentang materi ekosistem untuk peserta didik di SMA. Penelitian ini adalah penelitian pengembangan dengan model ADDIE (Analyze, Design, Development, Implementation, Evaluation). Subjek penelitian adalah 2 orang dosen BiologiÂ  FMIPA UNP, 1 orang guru Biologi SMAN1 Payakumbuh. Data didapatkan dalam penelitian ini berupa data observasi dan data validitas. Penelitian ini menghasilkan E-Modul Interaktif Menggunakan Smart Apps Creator Bermuatan Pendekatan kontekstual tentang Materi Ekosistem untuk Peserta Didik di SMA.